1982
DOI: 10.1017/s0007485300010609
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the flight of black-flies (Diptera: Simuliidae). I. Flight performance ofSimulium ornatumMeigen

Abstract: The flight performance of Simulium ornatum Mg. s.l. was measured under laboratory conditions using a simple flight mill. Males and unmated females were flown and the duration, distance and average speed of flight were recorded for adults fed on water only, sucrose, blood & water, or blood & sucrose. On 91% of all test occasions sucrose-fed insects flew but 25% of those on water only did not fly. Feeding flies on 10% sucrose solution markedly improved both willingness to fly and flight performance, and under th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
1

Year Published

1985
1985
2013
2013

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 23 publications
0
12
1
Order By: Relevance
“…The increased energy cost of reproductive development has been used to explain similar observations in other insect species (e.g. Dingle, 1966;Sharp et al, 1975;Cooter, 1982). Dispersal of mated females may best be undertaken before the first 3-4 days post-eclosion, because the increased wing loading (body weightiwing area) accompanying the production of eggs would lower flight performance after this time…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The increased energy cost of reproductive development has been used to explain similar observations in other insect species (e.g. Dingle, 1966;Sharp et al, 1975;Cooter, 1982). Dispersal of mated females may best be undertaken before the first 3-4 days post-eclosion, because the increased wing loading (body weightiwing area) accompanying the production of eggs would lower flight performance after this time…”
Section: Discussionmentioning
confidence: 95%
“…Another possibility is that this is not an artefact of tethering but reflects a biological difference between first and later flights. The first flight of tethered Simulium ornatum (Cooter, 1982) and Rhyacionia buoliana (Green, 1962) were also found to be the longest of a series of flights, and Johnson (1969) recognized that the first flight may be important in regard to dispersal.…”
Section: Discussionmentioning
confidence: 99%
“…Wind velocity has long been recognized as an important factor affecting flight. Laboratory studies have shown that the maximum flight speed of S.ornafum Meigen is 3 kmfh (Cooter, 1982) and 4 k d h for Xurcticum Malloch (Grace & Shipp, 1988). In the field, however.…”
Section: Discussionmentioning
confidence: 99%
“…The flight mills used were a modification of the system described by Cooter (1982Cooter ( , 1983, originally devised to study the flight performance of blackflies. The mill arm was lengthened to a radius of 23.9 cm and counterweighted at the end remote from the tethered insect to balance the greater weight of the moth.…”
Section: Methodsmentioning
confidence: 99%